2022
DOI: 10.32322/jhsm.1013908
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesic effectiveness of bilateral erector spinae plane block for adult cardiac surgery: a randomized controlled trial

Abstract: Introduction: There are few randomized controlled trials examining the effectiveness of bilateral Erector Spinae Plane Block (ESP) with patients undergoing cardiac surgery. The effect of bilateral ESP block on postoperative pain levels and analgesic consumption for patients undergoing open-heart surgery was examined in this single-blind, randomized, controlled trial.Material and Method: 54 patients who underwent cardiac surgery with open median sternotomy under general anesthesia between May 2020 and June 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Finally, we included 16 studies which included 1110 patients for analysis (489 in ESPB and 621 in control), [ Figure 1 ]. [ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ] Table 1 summarizes the details of all the studies included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we included 16 studies which included 1110 patients for analysis (489 in ESPB and 621 in control), [ Figure 1 ]. [ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ] Table 1 summarizes the details of all the studies included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported 24-hr morphine consumption[ 14 15 16 17 18 19 20 21 ] and 5 studies[ 22 23 24 25 26 ] reported 48-hr opioid consumption. For 24-hr morphine consumption, there were 232 patients in ESPB group and 240 patients in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, plane blockers applied to the thoracic wall have been widely accepted in recent years. In addition, these blocks have become an indispensable part of the concept of acceleration of recovery after thoracic surgery (ERATS) due to the potential for thoracic epidural analgesia and less side effects compared to thoracic paravertebral blocks (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Bukağıkıran et al (19) found that opioid consumption at the postoperative 24 th hour in patients undergoing thoracic surgery was significantly lower in the ESPB administered group than in the control group. There are studies in the literature demonstrating that both ESPB and TEA reduce opioid consumption in the postoperative period after thoracic surgery (20,21). However, the number of studies comparing these two blocks is limited.…”
Section: Discussionmentioning
confidence: 99%